Shrinkage Effects of Using Fly Ash instead of Fine Aggregate in Concrete Mixtures - Dongsheng Zhang; Pengfei Han; Qiuning Yang; Mingjie Mao (Advances in Materials Science and Engineering)
China is the world’s largest emitter of fly ash, an industrial by-product of coal combustion. Motivated towards greener development, China’s engineering industries must determine how to effectively utilize this by-product, while ensuring environmental and public safety protections. This study investigated the use of fly ash instead of fine aggregate in concrete mixtures with a focus on concrete shrinkage. A series of experiments were performed in which fly ash substitution levels, water-binder ratios, and ambient humidities were each respectively and exclusively varied to determine changes in the concrete’s drying and autogenous shrinkages. Experimental results indicated that the substitution of fly ash consistently decreased the drying shrinkage relative to ordinary concrete; a substitution level of 25% optimally reduced the drying shrinkage by 20.81%. A substitution level of 15% decreased the autogenous shrinkage relative to ordinary concrete, whereas higher levels (25, 35, and 45%) increased it. Ambient humidities also affected the concrete shrinkage, but the water-to-binder ratio effects were negligible. Drying shrinkage largely occurred before 28 d, whereas autogenous shrinkage continued after 28 d. Based on these experimental results, we evaluated common theoretical shrinkage models and subsequently developed a modified shrinkage model for application to concrete containing fly ash as fine aggregate.